Les articles 16 à 22 de la Charte - Foucher, Pierre (Canadian Charter of Rights and Freedoms = Charte canadienne des droits et libertés, 2025)
"More than forty years after the enactment of the Canadian Charter of Rights and Freedoms, this landmark treatise examines the interpretation and application of the Charter by Canadian courts in both the private and criminal law spheres, as well as its impact on the Canadian legal system. Updated to reflect the most recent constitutional developments, Canadian Charter of Rights and Freedoms, 6th Edition + Charte canadienne des droits et libertés, 6e édition by Errol Mendes and Stéphane Beaulac offers a comprehensive review of the evolution of the Charter in the Canadian legal landscape.Since its first publication in 1982, this bilingual text has become an invaluable reference for constitutional law practitioners and students." – Publisher's website.